119k views
4 votes
What are the factors of the expression (y-2)(x+3)?

2 Answers

4 votes

Answer:

Something which is multiplied by something else. A factor can be a number, variable, term, or a longer expression

with this information we can conclude that the numbers 2 and 3 are factors

Explanation:

User Bobby Grenier
by
5.3k points
0 votes

Answer:

yx+3y-2x-6

Explanation:

Isolate by the x or y on one side of the equation.

First, used FOIL method.

FOIL METHOD

(A+B)(C+D)=AC+AD+BC+BD

A=y

B=(-2)

C=x

D=3

Rewrite the equation.

yx+y*3+(-2)x+(-2)*3

yx+3y-2x-2*3

Solve.

Multiply.

3*2=6

yx+3y-2x-6

As a result, the final answer is yx+3y-2x-6.

User Ygram
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.